Large Time Behavior of a Nonlinear Diffusion Equation with a Source (Journal of Partial Differential Equations, 1993)
In this paper we study the positive solutions of the nonlinear diffusion equation u_t - &#916u^m = u^{-p} in R^N in the class of functions with some prescribed growth rate as |x| &#8594 &#8734. We give a description of the large time behavior and show that it is determined by the competition between the diffusion and the source.